2022
DOI: 10.1108/aaaj-01-2022-5616
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the “theory is king” thesis in accounting research: the case of actor-network theory

Abstract: PurposeThis paper examines the influence of the normal science tradition, epitomized by the notion that “theory is king”, on contemporary accounting research and the epistemological tensions that may emerge as this idea is applied to particular ways of studying accounting. For illustrative purposes, the authors focus on research informed by actor-network theory (ANT) which can be seen as an “extreme case” in the sense that it is, in principle, difficult to reconcile with the normal science aspirations.Design/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 109 publications
(323 reference statements)
0
7
0
Order By: Relevance
“…However, previous inquiries into the burdensome nature of reporting requirements have suggested that the concerns expressed by participants in this research are widely held (Dwyer et al, 2009(Dwyer et al, , 2020Moran et al, 2014). A further limitation of this study is its focus on empirical and practitioner rather than theoretical contributions, in line with its ANT ontological foundation (Lukka et al, 2022). While such limitations were addressed by engaging deeply within an under-researched sector, further research is encouraged to build on this preliminary work.…”
Section: Contributions and Future Researchmentioning
confidence: 92%
“…However, previous inquiries into the burdensome nature of reporting requirements have suggested that the concerns expressed by participants in this research are widely held (Dwyer et al, 2009(Dwyer et al, , 2020Moran et al, 2014). A further limitation of this study is its focus on empirical and practitioner rather than theoretical contributions, in line with its ANT ontological foundation (Lukka et al, 2022). While such limitations were addressed by engaging deeply within an under-researched sector, further research is encouraged to build on this preliminary work.…”
Section: Contributions and Future Researchmentioning
confidence: 92%
“…In many cases, this attitude comes with the assumption that every qualitative research paper – including literature reviews – needs to be theory-led, and thus, must adopt a theoretical lens to start with and preferably develop the theory further (cf. Lukka et al , 2022; see also Section 4.3). According to Keating (1995), theory development in qualitative accounting research occurs in three steps of the research process: theory discovery; theory refinement; and theory testing. …”
Section: Challenges Potential Solutions and Opportunities For Reviews...mentioning
confidence: 98%
“…Just as for empirical papers, accounting journals typically require from a review article a “contribution in its own right”. Indeed, given the important role of theory in qualitative accounting research (see Section 4.1; Lukka et al , 2022; Pfister et al , 2022), in my experience, this should preferably be a theoretical contribution and most often a contribution toward theory refinement (cf. Keating, 1995; Sutton and Staw, 1995).…”
Section: Challenges Potential Solutions and Opportunities For Reviews...mentioning
confidence: 99%
“…3. Modell et al (2017) and Lukka et al (2022) use the terms “performative” and “performativity” as the central theme of the paper, but they are excluded from our sample because they discusses all foundational perspectives of performativity rather than explicitly highlighting the particular angle of performativity used in their study.…”
Section: Notesmentioning
confidence: 99%